Characteristics of intimate partner violence in Mato Grosso do Sul state, Brazil, 2009-2018 - Jacqueline dos Santos; Cleber Nascimento do Carmo (Ministério da Saúde do Brasil, 2023)
Abstract Objective: to analyze intimate partner violence (IPV) in Mato Grosso do Sul state, Brazil, with emphasis on physical violence. Methods: this was a cross-sectional study applying multiple correspondence analysis (MCA) to records retrieved from the Notifiable Health Conditions Information System covering the period from 2009 to 2018. Results: of the 9,950 notifications registered, 91.8% were notifications of physical violence; higher rates were found in young females (189.2/100,000), who had up to incomplete high school education (139.6/100,000), had a partner (202.7/100,000), were Indigenous (488.8/100,000), and were living on the border with other countries (223,1/100,000); the aggressors were mostly current partners (76.9%) and male (95.5%); MCA revealed that physical violence was predominant at weekends, at night, with use of physical force and when the aggressor was under the influence of alcohol; most IPV did not occur at home, but was committed by current partners and was not a repeated event. Conclusion: IPV stood out among young victims, those who had a partner, low education, Indigenous women and occurred notably in the border region.